Blow-Up Phenomena for Porous Medium Equation with Nonlinear Flux on the Boundary - Yan Hu; Jing Li; Liangwei Wang (Journal of Applied Mathematics)
We investigate the blow-up phenomena for nonnegative solutions of porous medium equation with Neumann boundary conditions. We find that the absorption and the nonlinear flux on the boundary have some competitions in the blow-up phenomena.